Data management and analytics for medicine and healthcare : third International Workshop, DMAH 2017, held at VLDB 2017, Munich, Germany, September 1, 2017, Proceedings /: third International Workshop, DMAH 2017, held at VLDB 2017, Munich, Germany, September 1, 2017, Proceedings. (2017) - Unknown
No abstract available